If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(7y + -9) = -24 Reorder the terms: -2(-9 + 7y) = -24 (-9 * -2 + 7y * -2) = -24 (18 + -14y) = -24 Solving 18 + -14y = -24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -14y = -24 + -18 Combine like terms: 18 + -18 = 0 0 + -14y = -24 + -18 -14y = -24 + -18 Combine like terms: -24 + -18 = -42 -14y = -42 Divide each side by '-14'. y = 3 Simplifying y = 3
| (-5-3x)4-2x=0 | | 1/2h+1/3(h-7)=5/6h+2 | | -5x+4y=-10 | | 93+(-69)-21= | | 400n=0 | | 1(9a-2)=8a | | 24=2a+4a | | 16x^2+80x-64=0 | | 5x=9.25 | | 8=-5(-2)+3 | | -3s-9s=26 | | 2b-b+5b=16-16 | | 5x=9.75 | | 9x-2+4x=128 | | 55/2.5 | | 11-48=5(x-1)-7 | | 3/4-1/2y-5=7 | | 4-x/5=10 | | 2(1-3c)=-29 | | 4x^2+52x+160=0 | | Findx+5=25 | | (-95)+83+(-31)= | | 2y+7=5+2y+2 | | -8b-3-5=-35 | | 6(4v+2v)= | | -7(x+2)-13=21+8 | | 8x^2-56x-144=0 | | 9x-2+4x=180 | | -5=x/-7 | | -4(2x+3)=5x-1 | | w^2+4w-117=0 | | 4(x)+x=180 |